An open‐label, phase 1 study to evaluate the effects of hepatic impairment on edoxaban pharmacokinetics and pharmacodynamics. (2nd July 2015) - Mendell, Jeanne; Johnson, Lisa; Chen, Shuquan
Abstract: Edoxaban, a once‐daily, oral, direct factor Xa inhibitor, is approved for stroke prevention in nonvalvular atrial fibrillation and venous thromboembolism treatment. This study examined the effects of mild or moderate hepatic impairment on the pharmacokinetics of edoxaban and its metabolite M4. Thirty‐three subjects enrolled in 4 treatment cohorts—mild hepatic impairment (n = 8), moderate hepatic impairment (n = 9), and 2 cohorts of healthy controls matched for age, sex, and weight (each n = 8)—and received a single 15‐mg dose of edoxaban. Plasma pharmacokinetics for edoxaban and M4, prothrombin time (PT), activated partial thromboplastin time (aPTT), and safety data were measured over 72 hours. Edoxaban and M4 exposures were similar in subjects with mild or moderate hepatic impairment compared with matched controls. Higher PT and aPTT values were observed at baseline and after edoxaban dosing in the hepatic impairment groups compared with healthy controls. Edoxaban 15 mg was well tolerated in all cohorts. These results suggest that edoxaban exposure does not significantly increase in patients with mild or moderate hepatic impairment. However, because of the potential for underlying coagulopathy, edoxaban is not recommended for use in patients with moderate or severe hepatic impairment. No dose reduction is recommended for patients with mild hepatic impairment.